Sex and disability - McRuer, Robert; Mollow, Anna (Duke University Press, 2012)
The title of this collection of essays, Sex and Disability, unites two terms that the popular imagination often regards as incongruous. The major texts in sexuality studies, including queer theory, rarely mention disability, and foundational texts in disability studies do not discuss sex in much detail. What if'sex'and'disability'were understood as intimately related concepts? And what if disabled people were seen as both subjects and objects of a range of erotic desires and practices? These are among the questions that this collection's contributors engage. From multiple perspectives—including literary analysis, ethnography, and autobiography—they consider how sex and disability come together and how disabled people negotiate sex and sexual identities in ableist and heteronormative culture. Queering disability studies, while also expanding the purview of queer and sexuality studies, these essays shake up notions about who and what is sexy and sexualizable, what counts as sex, and what desire is. At the same time, they challenge conceptions of disability in the dominant culture, queer studies, and disability studies.Contributors. Chris Bell, Michael Davidson, Lennard J. Davis, Michel Desjardins, Lezlie Frye, Rachael Groner, Kristen Harmon, Michelle Jarman, Alison Kafer, Riva Lehrer, Nicole Markotić, Robert McRuer, Anna Mollow, Rachel O'Connell, Russell Shuttleworth, David Serlin, Tobin Siebers, Abby L. Wilkerson
Le texte Siebers, T. (2012). A sexual culture for disabled people a été donné à lire au cours sex1920. Le texte Mollow, A. (2012). Is Sex Disability? Queer Theory and the Disability Drive a été donné en lecture au cours SEX1920.
Keywords: approches et analyses; arts; autobiographie; capacitisme; cours; discipline; ethnographie; premier cycle; queer; ressource en ligne; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Par les mains pour les yeux : les représentations de l'identité sourde au sein de performances artistiques de la scène montréalaise - Paradis-Vigneault, Marie-Claude (Université Laval, 2012)
Ce mémoire s’appuie sur une recherche ethnographique réalisée principalement au sein de la communauté sourde de Montréal et tente de déceler les représentations de l’identité sourde au sein de performances artistiques de la scène montréalaise. Le but de cette recherche est d’inscrire la culture sourde dans les réflexions sociales et scientifiques portant sur l’expression identitaire de minorités culturelles par les arts. Afin de démontrer les liens à la fois théoriques et pratiques entre l’identité sourde et celles de minorités socio- politiques, telles que les Noirs, les gays, les femmes ou les Queers, cette étude s’appuie sur les concepts de performativité (Judith Butler), de performance (Clifford Geertz et Victor Turner) et de représentations (Stuart Hall et Serge Moscovici). Y seront également démontrées les relations entre ces notions, le vécu des sujets, leur agency et leur expression artistique.
http://hdl.handle.net/20.500.11794/23701
Keywords: amériques; anthropologie; approches et analyses; capacitisme; danse; discipline; histoire et politique; montréal; mémoires/thèses; performativité; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; théâtre; étude qualitative